Penguatan Pendidikan Karakter (PPK) dalam Pembelajaran Tematik Kelas V Sekolah Dasar - Niki Hidayah; Muhammad Suwignyo Prayogo (Elementar : Jurnal Pendidikan Dasar, 2022)
The purpose of this study is to describe the strengthening of Character Education in Thematic Learning at SD. The data collection technique uses passive participatory observation, in-depth interviews, and documentation. Data analysis techniques using interactive analysis Miles Huberman. The results showed that the strengthening of the character model. Strengthening character education in thematic learning at SD, there are two basic programs, namely the curriculum and the hidden curriculum, which in implication form the personality and character of students in everyday life. Examples of religious characters in each initial activity before learning are the Koran and prayer. Then the obligation to say hello when meeting friends or teachers is proven by religious programs. An example of the character of nationalism is in extra work programs such as scouts, PMR and paskibraka.